Descriptions of a new species of Callogobius with a congeneric new record and comments on previous records of the genus from Taiwan - Li, Hsien-En; Chen, I-Shiung (Zootaxa, 2024)
A new species of Callogobius from Taiwan, Callogobius aquilus sp. nov., is formally described herein. The new species can be characterized by the following unique combination of characters: D VI-I, 9; A I, 7; P1 16; P2; I, 5; LR 27–28 (modally 27); TR 9–10 (modally 9); D-P 5; Pred 11–12 (modally 12); V 10+16=26 and its own specific head lateral-line system and coloration pattern. Among the congeners, Callogobius aquilus sp. nov. can be clearly separated from its closely related species—C. sheni—by very conspicuous differences in both cephalic sensory canal pore patterns and blotch patterns. A brief comparison of the new species with other congeners will also be provided. Descriptions of the new species are then followed by the new record of Callogobius clitellus, which is only known from southern Taiwanese waters. The valid taxonomic records of nominal Callogobius species from Taiwan are discussed.